PELATIHAN MEMBUAT ALAT PERMAINAN EDUKATIF UNTUK PENGEMBANGAN KEMAMPUAN BERHITUNG PERMULAAN BAGI ANAK USIA DINI - Beata Palmin; Felisitas Ndeot; Maria Rahayu Anwar (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
Preliminary numeracy skills are very important to develop from early childhood. This ability is needed in everyday life, especially the concept of numbers which is also the basis for developing mathematical skills. The development of preliminary numeracy skills in early childhood must be done through fun play activities and using interesting educational play tools. However, the lack of availability of educational play tools plus limited financial capacity is still an urgent problem for almost all early childhood education institutions. This condition is exacerbated by the fact that many early childhood education teachers are not creative because of their limited knowledge and experience in providing educational game tools independently by utilizing existing tools and materials. A similar condition is experienced by teachers who are members of the cluster work center organization Ca Nai Cibal. This training activity aims to add insight and increase the creativity of early childhood education teachers in the cluster work center organization Ca Nai Cibal in making an appropriate educational play tools, especially for the development of preliminary numeracy skills. The methods used are: a) Focus Group Discussion (FGD) to explore the experiences of teachers regarding the overall picture of learning activities that have been taking place in their respective institutions, b) lectures are used to introduce the concept of the importance of APE for stimulating early childhood student cognitive development and use of educational play tools in supporting the optimization of the development of preliminary numeracy skills. c) performance/ performance of making various educational play tools using a variety of used goods that have been prepared. The results of the activities carried out, the teachers gained knowledge and skills about the function of educational play tools and their use in developing the cognitive aspects of early childhood, gained new knowledge and skills about the benefits of used household goods in making simple educational play tools, and were able to produce educational play tools, both by imitating and based on their own ideas. -Each by using used goods, such as: cardboard, plastic bottle caps, egg boards and others.